C++ reactive programming : design concurrent and asynchronous applications using the RxCpp library and modern C++17 - Pai, Praseed; Abraham, Peter (Packt, 2018)
Reactive programming is an effective way to build highly responsive applications with an easy-to-maintain code base. This book covers the essential functional reactive concepts that will help you build highly concurrent, event-driven, and asynchronous applications in a simpler and less error-prone way.